Activation of O2 across a C(sp3)–C(sp3) bond. Issue 19 (3rd February 2022) - Kumar, Rahul; Richter, Stefan; Maity, Suvendu; Sarkar, Pallavi; Chrysochos, Nicolas; Pati, Swapan K.; Ghosh, Prasanta; Schulzke, Carola; Jana, Anukul
Abstract : Molecular dioxygen is activated across the C(sp 3 )–C(sp 3 ) bond of a piperazine derivative. This unprecedented reaction proceeds without any catalyst and at ambient condition yielding a 8-membered cyclic organic peroxide. Abstract : The activation of atmospheric molecular dioxygen (O2 ) is reported, which occurred across a C(sp 3 )–C(sp 3 ) bond of a piperazine derivative without any catalyst at ambient conditions under the formation of 1, 2, 4, 7-dioxadiazoctane, an 8-membered (larger-ring) cyclic organic peroxide.